2011
DOI: 10.1111/j.1600-051x.2011.01760.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effect of autologous platelet-rich fibrin in the treatment of intra-bony defects: a controlled clinical trial

Abstract: Within the limit of the present study, there was greater reduction in PD, more CAL gain and greater intra-bony defect fill at sites treated with PRF than the open flap debridement alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
168
2
11

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(212 citation statements)
references
References 34 publications
19
168
2
11
Order By: Relevance
“…8,9 PRF has been used in different surgical procedures such as sinus floor augmentation, treatment of gingival recession (GR), furcation defects, maxillary rehabilitation before implant placement, restoration of peri-implant defects, as well as healing of extraction sockets with promising results. 10,11,12,13,14 In addition, certain clinical studies have been conducted on the use of PRF for treatment of intra-bony defects in humans, 15,16,17,18,19 but none have investigated its additive effects with ABBM for treatment of intra-bony defects. Thus, the present split-mouth, single-centre, controlled study aimed to compare the healing of intra-bony defects treated with a combination of ABBM-PRF or ABBM alone; the hypothesis being tested was that PRF would augment the regenerative effects of ABBM in human intra-bony defects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 PRF has been used in different surgical procedures such as sinus floor augmentation, treatment of gingival recession (GR), furcation defects, maxillary rehabilitation before implant placement, restoration of peri-implant defects, as well as healing of extraction sockets with promising results. 10,11,12,13,14 In addition, certain clinical studies have been conducted on the use of PRF for treatment of intra-bony defects in humans, 15,16,17,18,19 but none have investigated its additive effects with ABBM for treatment of intra-bony defects. Thus, the present split-mouth, single-centre, controlled study aimed to compare the healing of intra-bony defects treated with a combination of ABBM-PRF or ABBM alone; the hypothesis being tested was that PRF would augment the regenerative effects of ABBM in human intra-bony defects.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in concordance with those of the aforementioned studies. 36,37 Several studies 15,16,17,38 have examined the suitability of autologous PRF for treatment of human intra-bony defects and revealed that PRF improves clinical 15 and radiographical 15,16,17,38 parameters. However, in the present study, no statistically significant differences were observed between both groups, except for the significant CAL gain noted in the test group.…”
mentioning
confidence: 99%
“…As a result of treatment and 12 months follow-up, the defect was almost completely eliminated and satisfactory healing of periodontal tissues was observed. In the literature, there are also existing reports utilizing the required size PRF as filler into the infrabony defect and also placing the remaining part of the material to cover the same region as a barrier, successfully [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Un solo estudio trató defectos de 3 paredes (18) mientras que los otros 2 abordaron defectos de 2 y 3 paredes conjuntamente (19,20) . En el trabajo de Thorat y col. (2011), casi el 70% de los sitios correspondieron a 3 paredes (20) .…”
Section: ) L-prf Vs Colgajo De Acceso Periodontal (Cpa)unclassified